"You're fat and not normal!" From Body Image to Decision of Suicide - Lailatul Fitriyah; Tristan Rokhmawan (Indonesian Journal of Learning Education and Counseling, 2019)
Bullying has become a highlighted problem in recent years by observers (or researchers) about education, counseling, psychology, and the development of children and adolescents. One of the things that attracts attention is bullying with the theme of form and weight. Physical differences in the body, especially in obese people, are followed by stigma and negative justification. Internalization of stigma and justification leads to cases of oppression, in some cases, even suicide decisions. The author tries to find a network of theoretical and conceptual relationships between body image, diet, bullying, the role of the media, depression, to the decision to commit suicide from various sources and the results of previous studies. In the end, it seems that the habit of mocking and humiliating someone who is overweight, which we often face every day and is considered normal, can be a more serious problem. Being slim and fat is an option, but setting it as a normal standard can bring stereotypical havoc.